How to drink : a classical guide to the art of imbibing - Opsopoeus, Vincentius, -asi 1548 (Ancient wisdom for modern readers, 2020)
"Description A spirited new translation of a forgotten classic, shot through with timeless wisdom Is there an art to drinking alcohol? Can drinking ever be a virtue? The Renaissance humanist and neoclassical poet Vincent Obsopoeus (ca. 1498-1539) thought so. In the winelands of sixteenth-century Germany, he witnessed the birth of a poisonous new culture of bingeing, hazing, peer pressure, and competitive drinking. Alarmed, and inspired by the Roman poet Ovid's Art of Love, he wrote The Art of Drinking (De Arte Bibendi) (1536), a how-to manual for drinking with pleasure and discrimination. In How to Drink, Michael Fontaine offers the first proper English translation of Obsopoeus's text, rendering his poetry into spirited, contemporary prose and uncorking a forgotten classic that will appeal to drinkers of all kinds and (legal) ages. Arguing that moderation, not abstinence, is the key to lasting sobriety, and that drinking can be a virtue if it is done with rules and limits, Obsopoeus teaches us how to manage our drinking, how to win friends at social gatherings, and how to give a proper toast. But he also says that drinking to excess on occasion is okay-and he even tells us how to win drinking games, citing extensive personal experience. Complete with the original Latin on facing pages, this sparkling work is as intoxicating today as when it was first published".